Pengaruh Pendidikan Kesehatan dengan Media E-book terhadap Pengetahuan dan Sikap tentang Anemia pada Remaja Putri - Nia Anggi Lestari; Sri Sumarni; Fina Nurul Azizah (Journal of Midwifery Science: Basic and Applied Research, 2025)
The survey results found that as many as (32.0%) adolescent girls experienced anemia in Indonesia. Anemia causes negative impacts in the short and long term in adolescent girls and women of childbearing age. One way to overcome anemia is the use of media in education, which can be explained how to instill and develop knowledge and attitudes in adolescents so that they are aware and care about good nutritional health to prevent anemia. The purpose of this study is to find out the influence of health education with e-book media on knowledge and attitudes about anemia in adolescent girls. This research was conducted in the Semarang city area. This study uses Quasy experimental design nonequivalent control group design. The sample was selected using a total sampling technique totaling 61 respondents. Data analysis using the Wilcoxon test. The results of the study show that there is an influence of health education with e-book media on increasing knowledge and attitudes about anemia. With increased knowledge (p-value = 0.000) and attitude (p-value = 0.000). And there was a difference in influence between the two groups of p-value 0.000 on knowledge and p-value 0.000 on attitude. The results of this study are expected to increase the awareness and knowledge of adolescent girls about anemia, become a strategic reference for health workers in policy making, provide a foundation for the development of further research, and encourage Islamic boarding schools to create an environment that supports adolescent health and nutrition optimally.